1086. Impact of Systematic Thoraco-Abdomino-Pelvic CT Scan on the Diagnosis of Infective Endocarditis. (26th November 2018) - Lecomte, Raphaël; Issa, Nahema; Turnier, Paul Le; Gaborit, Benjamin; Deschanvres, Colin; Asseray, Nathalie; Camou, Fabrice; Boutoille, David
Abstract: Background: The incidence of embolic events (EE) is high in patients with infective endocarditis (IE). EE influence patient management in different settings because they are minor criteria in the Duke classification and may lead to changes medical therapy or surgical strategy. If current guidelines suggest that systematic thoraco-abdominopelvic CT scan (TAP-CT) may be helpful, reliable data are lacking. The main objective of this study was to describe how systematic TAP-CT affects the diagnosis of patients with IE. Secondary objectives were to assess the impact of the TAP-CT on the management of patients with IE and the incidence of contrast-induced acute kidney injury (CI-AKI). Methods: In this multicenter cohort study between January 2013 and July 2016, we included consecutive patients who had definite or possible acute IE according to the Duke-modified criteria, and after validation by the endocarditis teams. The main exclusion criterion was the absence of TAP-CT scan. We compared the Duke classification diagnosis data and treatment data (medical and/or surgical) regarding the presence or the absence of EE on the CT and investigated the tolerance of this examination as well. Results: Of the 522 patients included in this study, 217 (41.6%) had one or more EE on the TAP-CT. The two major Duke modified criteria were found in 397 patients (76, 1%) and 457 patients (87, 6%) had a definite endocarditis. On the basis of TAP-CT results in asymptomatic patients, diagnostic classification was upgraded from possible endocarditis to definite endocarditis for only four cases which represent 0.8% of the population. The presence of EE on CT did not modify the duration of antibiotic treatment ( P = 0.55) and the decision of surgical treatment ( P = 0.39). Specific treatment of the EE was necessary in 42 patients (8.0%) but only nine of these EE (1.9%) were asymptomatic. CI-AKI was observed in 78 patients (14.9%). Conclusion: The CT-scan findings slightly affected diagnosis of IE. The impact on the therapeutic management is low and the incidence of CI-AKI should not be underestimated. Additional studies are needed to assess whether CT-scan improves patient outcomes, leads to unnecessary procedures and increased costs. Disclosures: All authors: No reported disclosures.